Approach to Manage Congenital Absence of Anterior Cruciate Ligament in a 13 years old Patient – A Rare Case Report of Eastern India - Sahu, Santosh Kumar; Jeetendra, Chekuri; Raulo, Binod Chandra; Kar, Dattatreya; Dash, Aniruddh (AL-Kindy College Medical Journal, 2023)
Congenital absence of anterior cruciate ligament is highly uncommon occurrence. It has since been documented as a standalone anatomical entity or, more frequently, in conjunction with other congenital anomalies. Surgical treatment for this patient population has only been reported in very few cases. In this article, we share our experience in managing a case of unilateral congenital deficiency of anterior cruciate ligament (ACL) in a 13 years old female patient by physeal sparing arthroscopic ACL reconstruction, using All-inside technique.